Colchicine-Induced Phenotypic Alterations in Dendrobium 'Transient White Rika' and 'Florenza': Valuable Material for Genetics-Based Learning Modules - Dwi Sucianingtyas Sukamto; Sarwo Danuji; Hanif Rafika Putri; Nurul Komaria (Postgraduate, University of Mataram, 2025)
This study investigates the phenotypic alterations in Dendrobium 'Transient White Rika' (RKA) and 'Florenza' (FLO) orchids resulting from colchicine-induced polyploidy during in vitro cultivation. Colchicine, a known mitotic inhibitor, was applied at varying concentrations (0 ppm, 4000 ppm, 5000 ppm, 6000 ppm) to induce chromosome doubling and assess its impact on the vegetative and generative phases of the orchids. A factorial Randomized Block Design (RBD) was employed to analyze the effects of these treatments. The study revealed significant variations in leaf length and color, particularly at higher colchicine concentrations. Morphological changes were most pronounced at 6000 ppm, where the leaf length decreased, and flower morphology exhibited unique features compared to the control. The study also observed a reduction in stomatal density as colchicine concentration increased, correlating with an enlargement of leaf epidermal cells. These findings indicate that colchicine treatment can effectively induce phenotypic changes in Dendrobium orchids, contributing to the development of hybrids with superior ornamental qualities. However, the study also notes that the response to colchicine is variable, with certain parameters like the number of new shoots and leaf width not showing significant changes. The results underscore the potential of colchicine-induced polyploidy in orchid breeding, though further research is necessary to optimize treatment protocols and ensure the stability and viability of the resulting hybrids. These findings may serve as valuable material for genetics-based learning modules in biology.